Bakhtin’s Dialogue as Supply Chain Value of the Contemporary Humanities - Somkin, Alexander A.; Somkina, Alla N (International Journal of Supply Chain Management, 2020)
Abstract The article gives a short review on fundamentally new ideas, which were advanced by Mikhail Bakhtin in different spheres of socially humanitarian cognition based on the supply chain strategy. It is about the supply chain strategy in philosophical anthropology and ethics. The idea of the integrated approach to the study of human; in social philosophy and axiology – the priority of universal humanistic values. In cultural studies – the unity and diversity of world culture and the importance of a constructive dialogue between nations; the theoretical foundations of the “laughter and carnival culture”; in literary criticism – a dialogic understanding of an author and a hero of a narration; in stylistics – the problems of modern speech genres and the meta-language of texts. In the given article we consider the principle of “dialogic thinking” as the main methodological discovery made by M. Bahtin. Based on the method of logical extrapolation, the authors put forward the provisions on the further development of Bakhtin’s principle of “dialogical thinking” in its relation to the current humanitarian problems.